Reinterpretasi Spiritualitas Bate dalam Pemberkatan Gereja Katolik di Tana Toraja: Telaah Hermeneutik - Abraham, Agustinus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the spirituality of the bate symbol within the context of the blessing of Catholic church buildings in Tana Toraja as a concrete form of inculturation of the Christian faith into local culture. Originally, bate functioned as a religious symbol in traditional Toraja ceremonies for inaugurating tongkonan (ancestral houses). Over time, however, this symbol has been adopted and reinterpreted in Catholic liturgical celebrations, particularly during church blessing rituals. The study employs a qualitative method using a literature review and applies Paul Ricoeur’s hermeneutical framework, which consists of three stages: the world of the interpreter, the world of the text, and appropriation. The analysis reveals that bate can be understood as a cultural text rich in spiritual meaning. Traditionally, it symbolizes a connection between heaven and earth as well as cosmic power. Within the perspective of Christian inculturation, bate undergoes symbolic reinterpretation, representing values of faith such as the Trinity, the cross, the Eucharist, the Holy Scripture, and Jesus Christ as the mediator of salvation. The incorporation of bate in Catholic liturgy is not merely a cultural adaptation but a tangible manifestation of the encounter between faith and culture, achieved in a contextual and symbolic manner within Torajan society. This study affirms the significance of inculturation in proclaiming the Gospel in a way that is relevant and grounded, without compromising the core essence of Catholic faith. Furthermore, it recommends further research on other local symbols to enrich the dialogue between faith and culture in pastoral contexts.